2022 IEEE International Conference on Nanoelectronics, Nanophotonics, Nanomaterials, Nanobioscience &Amp; Nanotechnology (5NANO 2022
DOI: 10.1109/5nano53044.2022.9828977
|View full text |Cite
|
Sign up to set email alerts
|

RF Performance Assessment of Sub-8nm GaN-SOI-FinFET Using Power Gain Parameters

Abstract: This work presents, a radio frequency (RF) performance evaluation of nanoscale gallium nitride-silicon-oninsulator fin field-effect transistor (GaN-SOI-FinFET). All the results have simultaneously been compared with conventional FinFET (Conv. FinFET). All the results show that the power gains have significantly improved in terms of Gma (maximum available power gain), Gms (maximum stable power gain), stern stability factor, GMT (maximum transducer power gain), and an appreciable reduction in intrinsic delay as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Kstable values for varied temperatures are drawn from the small-signal yparameters to analyze the device reliability [28]. It is observed that Kstable > 1 at greater frequencies, however, a small change of 12% in critical frequency is notable at Kstable=1 as the temperature falls from 400 K to 50 K denoting improved RFstable device at DCT [29][30].…”
Section: Impact Of Dct On Rf Metricsmentioning
confidence: 99%
“…Kstable values for varied temperatures are drawn from the small-signal yparameters to analyze the device reliability [28]. It is observed that Kstable > 1 at greater frequencies, however, a small change of 12% in critical frequency is notable at Kstable=1 as the temperature falls from 400 K to 50 K denoting improved RFstable device at DCT [29][30].…”
Section: Impact Of Dct On Rf Metricsmentioning
confidence: 99%